Genome-wide analysis of lncRNA and mRNA expression and endogenous hormone regulation during tension wood formation in Catalpa bungei - Yao Xiao; Fei Yi; Juanjuan Ling; Guijuan Yang; Na Lu; Zirui Jia; Junchen Wang; Kun Zhao; Junhui Wang; Wenjun Ma (BMC Genomics, 2020)
Abstract Background Phytohormones are the key factors regulating vascular development in plants, and they are also involved in tension wood (TW) formation. Although the theory of hormone distribution in TW formation is widely supported, the effects of endogenous hormones on TW formation have not yet been assessed. In this study, TW formation was induced in Catalpa bungei by artificial bending. The phytohormone content of TW, opposite wood (OW) and normal wood (NW) was determined using liquid chromatography-mass spectrometry (LC-MS), and transcriptome sequencing was performed. The hormone content and related gene expression data were comprehensively analyzed. Results The results of analyses of the plant hormone contents indicated significantly higher levels of cis-zeatin (cZ), indoleacetic acid (IAA) and abscisic acid (ABA) in TW than in OW. Genes involved in the IAA and ABA synthesis pathways, such as ALDH (evm.model.group5.1511) and UGT (evm.model.scaffold36.20), were significantly upregulated in TW. and the expression levels of ARF (evm.model.group5.1332), A-ARR (evm.model.group0.1600), and TCH4 (evm.model.group2.745), which participate in IAA, cZ and Brassinolide (BR) signal transduction, were significantly increased in TW. In particular, ARF expression may be regulated by long noncoding RNAs (lncRNAs) and the HD-ZIP transcription factor ATHB-15. Conclusions We constructed a multiple hormone-mediated network of C. bungei TW formation based on hormone levels and transcriptional expression profiles were identified during TW formation.